ЗАСТОСУВАННЯ ВЕЙВЛЕТ-ПЕРЕТВОРЕННЯ ДЛЯ ЗАХИСТУ ВІД ЗАМИКАННЯ ФАЗИ НА ЗЕМЛЮ В ЕЛЕКТРИЧНИХ МЕРЕЖАХ СЕРЕДНЬОЇ НАПРУГИ - Сивокобиленко, В.Ф.; Лисенко, В.А. (Інститут електродинаміки НАН України, Київ, 2021)
For electrical networks with voltage of 6-35 kV with a compensated, isolated or resistor-grounded neutral, a phase-to-ground protection has been developed, in which, based on the results of the time-frequency wavelet transform of zero-sequence currents, voltages and their derivatives, using the obtained analytical expression, the total reactive power wavelet for different frequencies is determined. It is shown that at the initial moment of a phase-to-ground fault on the damaged feeder the power is always positive, and on the undamaged feeder it is negative, regardless of the operating mode of the neutral. Wavelet transform coefficients are found by convolution of discrete values of measured signals with sine-cosine signals of the Morlet mother function. The time-reversed sequence of these signals is obtained using a matrix for which the rules for its formation are stated. An excess of the zero phase sequence voltage amplitude of the set value is used as a starting protection element. With the help of a mathematical model of the network, studies of the behavior of protection in case of blind and arc phase-to-ground faults at various degrees of compensation of capacitive currents, at various voltage values at the moment of the short circuit have been carried out. In all modes, a reliable protection operation is obtained, the sensitivity of which is an order of magnitude higher than the protection based on Fourier transforms. Positive results of testing a protection sample implemented on a microprocessor-based element base at a laboratory stand are obtained. References 20, figures 7, tables 2.